Adrian's Isagoge and the dianoia of scripture. (20th February 2023) - Toom, Tarmo
Abstract : A fifth-century handbook on Scripture and its interpretation, Adrian's Isagōgē in sacras scripturas, is the only known and extant introductio in Greek which represents the Antiochean exegetical tradition. This treatise, which is available in two recensions, is largely an explanation of the stylistic idiosyncrasies of Scripture's God-talk. Although Adrian acknowledges the fact that Scripture uses allegory to say various things (i.e., the compositional allegory), he discourages the use of allegory for interpreting that which Scripture says (i.e., interpretative allegory). This paper provides a critical assessment of Adrian's hermeneutical advice and argues that the proposed disambiguation methods are not really sufficient for addressing the question of adequate interpretation of Scripture.